Public Participation in Decision–Making Towards Accountable and Transparent Governance in Vietnam - Huong Thi Lan Phan (Jambe Law Journal, 2021)
Public participation is one of the key elements in ensuring democratic values in any country. People have the right to participate in the decision-making process and express their ideas and needs. While Vietnam has developed a legal framework for legislation that stipulates the obligation of drafting committees to open draft laws for public comment (Law on Promulgation of Normative Legal Documents 2015, amended 2020). However, Vietnamese citizens and legal entities still cannot participate in the drafting of laws and policies because many obstacles exist: (1) the law does not clearly define the authorities’ obligations to respond to people's comments/feedback; (2) there is a lack of an effective mechanism to ensure that individuals and organizations can participate in the decision-making process, especially in the pandemic situation - Covid 19; (3) there is a lack of an effective mechanism for policy impact assessment. Thus, the question is how to promote public participation in the decision-making process to ensure that policy meets the interests of the public and the needs of the people. This paper aims to assess the current situation of public participation in decision-making and propose solutions to develop active and meaningful participation of people in formulating problems, planning, implementing, and tracking the implementation of policies towards accountable and transparent governance in Vietnam.